In Vivo Assessment of Antioxidants and Antihyperglycemic Effect of Barleria cristata leaves in Streptozotocin- Induced Diabetic Rats - Rajasekaran, Narmadha; Duraisamy, Gomathi; Manokaran, Kalaiselvi; Kanakasapathi, Devaki (International Journal of Applied Sciences and Biotechnology, 2014)
Objective: Many new bioactive drugs isolated from plants having hypoglycaemic effects showed anti diabetic activity equal and sometimes even more potent than known oral hypoglycaemic agents. In this present study, designed to evaluate antihyperglycermic and antioxidants effect on ethanolic leaf extracts Barleria cristata (EtBc) in streptozotocin-induced diabetic rats at dose level 400mg/kg body weight for the treatment of 45 days. Method and materials: The experimental rats were randomly divided into five groups as a control, streptozotocin induced with diabetes (45mg/kg bw) without any treatment, treated with standard drug glibenclamide (1.25 mg/kg bw), EtBc (400 mg/kg bw) in diabetic induced rats and treated with EtBc alone without diabetic rats. At the end of 45th day animals were sacrificed, collect the serum, liver, kidney and pancreas for estimate the glucose, insulin, C-peptide, glycosylated hemoglobin, hemoglobin in serum, protein, enzymatic and nonenzymatic antioxidants and lipid peroxidation in tissues. Results: After the administration of EtBc, blood glucose levels were showed significantly reduction (P<0.05) in diabetic rats and it has been observed alternation occured in body and organ weight and it was also normalized the serum level of glycemic profile like insulin, C-peptide, total hemoglobin and glycosylated hemoglobin levels similar to that of control rats. Antioxidants enzymes were return to back their levels as control in different tissues when compared to diabetic rats and also observed no significance difference between control and EtBc alone group rats at the end of 45th day. Therefore it was suggested that Barleria cristata may act by potentiation of pancreatic secretion of insulin or increasing glucose uptake by muscle cells. Conclusion: In this study, suggested the efficacy of Barleria cristata proved the maintenance of glucose homeostasis and may be used as a therapeutic agent in the management of diabetes mellitus. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11219 Int J Appl Sci Biotechnol, Vol. 2(4): 437-445